2018
DOI: 10.1021/acs.est.7b06255
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Effects and Estrogenicity of Bisphenol A Alternatives in a Zebrafish Embryo Model

Abstract: In order to understand the negative effects of bisphenol A (BPA) alternatives comprehensively, zebrafish embryos were used to assess the lethality, developmental effects, and estrogenic activity of bisphenol analogues. The in silico estrogenic activities of bisphenol analogues were assayed by binding simulation. According to our results, the lethality of bisphenol analogues decreased in order of bisphenol AF (BPAF) > BPA > bisphenol F (BPF) > bisphenol S (BPS). BPAF and BPF induced significant effects on zebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
90
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(105 citation statements)
references
References 69 publications
14
90
0
1
Order By: Relevance
“…The National Health and Nutritional Survey (NHANES) done in 2013-2014 (Lehmler et al 2018) found detectable level of all three bisphenols (Mu et al 2018) in randomly selected urine samples collected from the U.S. population, indicating that the exposure to BPA and its substitutes is almost ubiquitous. The urinary levels of bisphenols were associated mainly with age, gender and race/ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…The National Health and Nutritional Survey (NHANES) done in 2013-2014 (Lehmler et al 2018) found detectable level of all three bisphenols (Mu et al 2018) in randomly selected urine samples collected from the U.S. population, indicating that the exposure to BPA and its substitutes is almost ubiquitous. The urinary levels of bisphenols were associated mainly with age, gender and race/ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Companies increasingly advertise for their BPA-free products (Websites European chemicals agency, Umweltbundesamt). What the consumers do not know is, that BPA is replaced by other bisphenols like bisphenol F or S that show comparable or even worse harmful developmental effects and are able to cross the placenta (156,157). It was recently shown that the exposure of the population to BPA substitutes is almost ubiquitous (158).…”
Section: Bpamentioning
confidence: 99%
“…BPF has been shown to significantly alter 56 different genes involved in the serotonin-dopamine pathway in the prefrontal cortex of female rats, changing the transcrip-tion of these genes (Castro et al, 2015). Studies with zebrafish embryos have revealed decreased heart rates, hatching inhibition, and disrupted development when treated with BPF (Mu et al, 2018). Similar to the mechanism proposed by the Kinch lab, BPF was shown to upregulate aromatase in the brain of embryonic zebrafish through estrogen receptors by acting as a full agonist in vivo (Le Fol et al, 2017).…”
Section: Introductionmentioning
confidence: 80%